NUMERIC DENTAL ANOMALIES IN CHILDREN FROM CLUJ-NAPOCA - Viorica Ţărmure; Radu Septimiu Câmpian; Victor Suciu; Ecaterina Ionescu; Elina Teodorescu; Ştefan Milicescu; Paula Jiman; Olimpia Bunta; Andreea Pop (Amaltea Medical Publishing House, 2018)
Numeric tooth anomalies involving a fewer number of teeth (hypodontia) are considered dental dystrophies determined by disturbances during the odontogenesis stage. The aim of this study was to investigate the incidence of the anomaly and its clinical manifestations in two representative groups of children: an unselective group (2017 children in Cluj-Napoca aged between 7 and 15) and a group of orthodontic patients (2,000 patients of the same ages, with various dental-maxillary anomalies), using the statistical validation test ANOVA. Our findings included a high incidence of hypodontia, with varied clinical aspects, a low addressability and "accidental" diagnosis during investigation for other anomalies.